HUBUNGAN OBESITAS DENGAN PREEKLAMSIA PADA IBU HAMIL TRIMESTER KETIGA DI WILAYAH KERJA PUSKESMAS LUBUK BAJA KOTA BATAM - Cindy Claudia Sianturi; Savitri Gemini; Roza Erda (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Prelelclampsia is a pregnancy complication that can increase maternity and feltal morbidity and mortality. Obesity is known as an important risk factor associateld with the incidence of preeclampsia. to determin the relationship between obesity and preeclamsia in third trimester pregnant women in the working area of Lubuk Baja Community Helalth Center, Batam City in 2025. This type of research use observationa with a cross-selctional design. Thel study population was all third trimester pregnant women in the working area of Lubuk Baja Community Health Center, with a sample of 41 respondents selelcteld through a purposivel sampling telchniquel. Data werel collelcteld using obselrvation shelelts and meldical relcords, then analyzeld univariatelly and bivariatelly with thel Chi-Squarel telst at a 95% confidelncel levell (α = 0.05). The results of univariate research showed that out of 41 pregnant women, the incidence of obesity in pregnant women in the third trimester was 25 pregnant women (61.0%) in the obesity category and 29 pregnant women (70.7%) in the mild preeclamsia category, while 12 pregnant women (29.3%) experienced severe preeclamsia in the working area of the Lubuk Baja Health Center, Batam City in 2025. Bivariate analysis showed a significant relationship between obesity and the incidence of preeclampsia in pregnant women in the third trimester (p = 0.000 0.05). Therelfore, it can bel concludeld that obesity has a significant rellationship with thel incidence of preeclamsia in prelgnant women in thel third trimelstelr in thel working area of thel Lubuk Baja Community Helalth Centelr, Batam City in 2025. Promotive and prelvelntivel elfforts are through nutrition education, welight control, and screlelning of prelgnant women to prelvelnt prelgnancy complicationsKeywords: Obesity, Preeclampsia,Third Trimester Pregnant Women